(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті обґрунтовано дидактичні умови ефективної побудови інформаційно-освітнього середовища вишу. Ключові слова: дидактичні умови, інформаційно-освітнє середовище. The didactic conditions of effective constructions of the information-educational environment of a higher educational institution are substantiated in the article. Key words: didactic conditions, the information-educational environment of a higher educational institution.